Thoracic epidural analgesia prolongs postoperative QT interval on electrocardiogram in major non-cardiac surgery: a randomized comparison and a prospective cohort analysis - Hori, Kotaro; Tsujikawa, Shogo; Egami, Mika; Waki, Sayaka; Watanabe, Ryota; Hino, Hideki; Matsuura, Tadashi; Mori, Takashi (Frontiers in Pharmacology, 2023)
Introduction: Prolongation of QT interval on electrocardiogram can be associated with perioperative lethal arrhythmia. Epidural analgesia is a commonly used modality to relieve surgical pain by blocking sensory nerves, which also blocks the autonomic nervous system and can affect QT interval. Since patient monitoring becomes much less frequent after surgery than intraoperative period, we investigated the effects of epidural analgesia on postoperative QT interval with a randomized clinical trial and a prospective cohort study. Methods: In a randomized study, we assigned 60 patients undergoing thoracic epidural analgesia to an epidural analgesia or no-epidural analgesia group, in which 3 ml/h of 0.25% epidural levobupivacaine (7.5 mg/h) was administered only in the epidural analgesia group during surgery. The primary outcome was the postoperative heart rate-corrected QT interval. In a prospective cohort study, patients were assigned to receive 5 ml/h epidural levobupivacaine (12.5 mg/h). The plasma concentration of levobupivacaine was measured using liquid chromatography-mass spectrometry. Results: The median postoperative corrected QT interval interval with 3 ml/h epidural levobupivacaine was significantly longer than that without epidural analgesia. Using multiple regression analysis for the factors known to affect postoperative corrected QT interval interval, epidural analgesia was found to be an independent variable for prolongation, and the mean difference of the corrected QT interval interval with or without epidural analgesia was 23 ms after adjustment. The median plasma concentration of levobupivacaine at the end of surgery was 164 ng/ml with 3 ml/h epidural levobupivacaine, and the correlation coefficient to the postoperative corrected QT interval interval was 0.14, showing a not significant correlation. A prospective cohort study showed that 5 ml/h epidural levobupivacaine significantly prolonged postoperative corrected QT interval interval compared to preoperative baseline. The median plasma concentration of levobupivacaine was 166 ng/ml with 5 ml/h, the correlation coefficient of which showed no significant correlation. Conclusion: Thoracic epidural analgesia could enhance postoperative corrected QT interval prolongation after general anesthesia. The mechanism is possibly caused by blocking neighboring or part of the cardiac sympathetic nerves, rather than by systemic effects of epidurally administered levobupivacaine. Clinical trial number: UMIN000013347 for the randomized study and UMIN000041518 for the prospective cohort study, which were registered at University hospital Medical Information Network Center.